2020
DOI: 10.3390/electronics9020250
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Planning Algorithm of UAV Based on System Positioning Accuracy Constraints

Abstract: This paper describes a novel trajectory planning algorithm for an unmanned aerial vehicle (UAV) under the constraints of system positioning accuracy. Due to the limitation of the system structure, a UAV cannot accurately locate itself. Once the positioning error accumulates to a certain degree, the mission may fail. This method focuses on correcting the error during the flight process of a UAV. The improved genetic algorithm (GA) and A* algorithm are used in trajectory planning to ensure the UAV has the shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…) to analyze and denoise measured data in a variety of applications and services (e.g., wind speed prediction, air quality prediction, underground mine applications, neural audio caption, etc.). Several practical experiments were given in these articles, and the results indicated that the performance of the improved deep learning methods could be higher than the performance of conventional machine learning methods [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) to analyze and denoise measured data in a variety of applications and services (e.g., wind speed prediction, air quality prediction, underground mine applications, neural audio caption, etc.). Several practical experiments were given in these articles, and the results indicated that the performance of the improved deep learning methods could be higher than the performance of conventional machine learning methods [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In their experiments, two practical case studies were selected to evaluate the improved genetic algorithm and the improved sparse A* algorithm. The results show that the trajectory length could be reduced by 57.79% by the proposed methods [47].…”
Section: Uav and Object Tracking Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Zhou et al 34 Hybrid GA and A* algorithm-based path planning results in high accuracy of path planning.…”
Section: Complex Calculation Processmentioning
confidence: 99%
“…In view of the abovementioned importance of studying path planning in UAVs, it is imperative when UAVs fly in cluttered environments that they have to proceed with their task while adhering to the operational restrictions and ensuring safe navigation concerning the encompassing objects. Different approaches to UAVs path planning and for various techniques of measurement employed by the UAVs are demonstrated in [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In addition, several inclusive reviews for path and trajectory planning were conducted for UAVs [ 25 ], ground vehicles [ 26 ], and mobile robots [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%